2015
DOI: 10.5897/jpbcs2015.0521
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sorghum (Sorghum bicolor L. Moench) landraces tolerant to post flowering drought stress using drought tolerance indices

Abstract: Drought stress occurring during the post-flowering growth stage of sorghum can cause considerable reduction in yield. In order to identify drought tolerant Eritrean sorghum landraces and assess efficiency of drought tolerance indices, twenty five sorghum (Sorghum bicolor L. Moench) accessions were evaluated in split plot design with three replications. Fully irrigated and drought stress treatments were assigned in main plot and the landraces were evaluated in sub plot for drought stress tolerance at post-flowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
3
2
0
1
Order By: Relevance
“…The seventh (PC VII) was explained negatively by the variations resulting from leaf colour and positively from grain lustre (Table 4). The principal components analysis clearly showed that the entire variation in the 642 sorghum germplasm lines cannot be explained on the basis of few characters and thereby a number of traits were involved in explaining the gross variance among the genotypes though with different magnitudes.Similar results were discussed in earlier studies in sorghum (Ayana and Bekele, 1999;Tesfamichael et al, 2015).…”
Section: Resultssupporting
confidence: 92%
“…The seventh (PC VII) was explained negatively by the variations resulting from leaf colour and positively from grain lustre (Table 4). The principal components analysis clearly showed that the entire variation in the 642 sorghum germplasm lines cannot be explained on the basis of few characters and thereby a number of traits were involved in explaining the gross variance among the genotypes though with different magnitudes.Similar results were discussed in earlier studies in sorghum (Ayana and Bekele, 1999;Tesfamichael et al, 2015).…”
Section: Resultssupporting
confidence: 92%
“…This, in turn, implies that several traits are involved in explaining the gross variance among genotypes. This further confirms previous results that also described the importance of these traits in contributing towards the overall diversity in sorghum 11,12 . Discriminant analysis revealed that 81% of the genotypes were correctly classified to their breeding groups.…”
supporting
confidence: 82%
“…Bello et al (2007) reported high value of PCV and GCV for panicle length per plant, 1000 seed weight, days to flowering and days to maturity (Kassahun et al, 2015), high PCV values (>20%) for leaf area index, plant height, panicle weight, panicle yield, grain yield and harvest index and relatively high GCV values (> 20%) for leaf area index, plant height, panicle yield, grain yield and harvest index. Tesfamichael et al (2015) also reported high magnitude of phenotypic and genotypic coefficient of variations for plant height, harvest index and biomass. In contrast to the present study, low GCV and PVC (<20%) was observed in terms of panicle length, number of seeds per panicle, plant height, days to maturity, 1000 seed weight except grain yield, biomass and harvest index (Table 3).…”
Section: Mean Estimates Of Variance Component Coefficients Of Variationmentioning
confidence: 99%